Bioethics education in clinical settings: theory and practice of the dilemma method of moral case deliberation. Issue 1 (December 2016) - Stolper, Margreet; Molewijk, Bert; Widdershoven, Guy
Abstract Background Moral Case Deliberation is a specific form of bioethics education fostering professionals' moral competence in order to deal with their moral questions. So far, few studies focus in detail on Moral Case Deliberation methodologies and their didactic principles. The dilemma method is a structured and frequently used method in Moral Case Deliberation that stimulates methodological reflection and reasoning through a systematic dialogue on an ethical issue experienced in practice. Methods In this paper we present a case-study of a Moral Case Deliberation with the dilemma method in a health care institution for people with an intellectual disability, describing the theoretical background and the practical application of the dilemma method. The dilemma method focuses on moral experiences of participants concerning a concrete dilemma in practice. By an in-depth description of each of the steps of the deliberation process, we elucidate the educational value and didactics of this specific method. Results The didactics and methodical steps of the dilemma method both supported and structured the dialogical reflection process of the participants. The process shows that the participants learned to recognize the moral dimension of the issue at stake and were able to distinguish various perspectives and reasons in a systematic manner. The facilitator played an important role in the learning process of the participants, by assisting them in focusing on and exploring moral aspects of the case. Discussion The reflection and learning process, experienced by the participants, shows competency-based characteristics. The role of the facilitator is that of a Socratic teacher with specific knowledge and skills, fostering reflection, inquiry and dialogue. Conclusion The specific didactics of the dilemma method is well suited for teaching bioethics in clinical settings. The dilemma method follows an inductive learning approach through a dialogical moral inquiry in which participants develop not only knowledge but also skills, attitude and character. The role of a trained facilitator and a specific view on teaching and practicing ethics are essential when using the dilemma method in teaching health care professionals how to reflect on their own moral issues in practice.